Review of existing methodologies to assess the activity of CYP2D6 using exogenous and endogenous markers - A. D. Abdrashitov; G. N. Gildeeva; G. V. Ramenskaya; V. V. Smirnov (Фармакокинетика и Фармакодинамика)
Peculiarities of functioning and polymorphism of cytochrome P450 isoenzyme CYP2D6. Existing methods for determining its activity using endogenous markers. A review of studies on the screening of endogenous substrates, biotransformation mainly under the influence of isoenzyme CYP2D6. The results by determination pinoline relationship to its metabolite 6-hydroxy-1,2,3,4-tetrahydro-beta-carboline in vitro in cell culture and in vivo in mice for evaluation isoenzyme activity CYP2D6.